Myasthenia Gravis - Silvestri, Nicholas J.; Wolfe, Gil I. (Seminars in Neurology, 2012)
Myasthenia gravis (MG) is the most common disorder of the neuromuscular junction (NMJ), with an estimated prevalence between 25 and 142 per million. It characteristically presents with fatigable weakness, often initially involving the ocular muscles and manifesting as intermittent ptosis and diplopia. Ultimately, the disease generalizes in two-thirds of patients, leading to weakness of bulbar, neck, limb, and respiratory muscles. The majority of patients with generalized MG, and roughly half of patients with purely ocular disease, harbor antibodies to skeletal muscle nicotinic acetylcholine receptors. A subset of patients with generalized disease have antibodies to muscle-specific receptor tyrosine kinase (MuSK). Acetylcholinesterase inhibitors are often the first modality of therapy for MG. As an immune-mediated disorder, MG can respond to several immunosuppressive agents, such as corticosteroids, azathioprine, mycophenolate mofetil, and cyclosporin. Thymectomy is a key component of management in appropriately chosen MG patients and those with thymoma. Newer or alternative immunotherapies including tacrolimus, rituximab, methotrexate, and complement inhibiting agents are an area of active investigation.
Keywords: myasthenia gravis; treatment; anticholinesterases; immunosuppression; thymectomy